OVERVIEW OF METHODS FOR SYNCHRONIZING WITH THE POWER GIRD (PLL) FOR POWER CONVERTERS - Lipnicki, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This paper deals with crucial aspect of synchronizing power converters connected to the utility grid. Today, many components of Distributed Power Generation Systems (DPGS), such as Flexible Alternating Current Transmission Systems (FACTS), traction applications and power line conditioners containing power converters, have an important demand for optimized synchronization algorithms. It should be noted that also Transmission System Operator have specific requirements for synchronization with the grid. One of the possible ways to achieve a good performance in terms of synchronization is to use a Phase Locked Loop algorithm (PLL). This paper shows the results of investigation on different PLL methods, explaining how they work along with a summary describing their features, possibilities and drawbacks. In the end the impact of voltage unbalances and harmonics on synchronization algorithms is analyzed. The PLL methods were evaluate by the means of simulations.